2013
DOI: 10.3390/cancers5041199
|View full text |Cite
|
Sign up to set email alerts
|

Three-Times Daily Ultrafractionated Radiation Therapy, A Novel and Promising Regimen for Glioblastoma Patients

Abstract: Glioblastomas are considered to be one of the most radio resistant tumors. Despite new therapies, the prognosis of this disease remains dismal. Also, the mechanisms of radiation resistance in mammalian cells are more complex than once believed. Experimental studies have indicated that some human cell lines are sensitive to low radiation doses of <1 Gy. This phenomenon has been termed low-dose hyper-radio-sensitivity (HRS), and is more apparent in radio resistant cell lines, such as glioblastoma cells. Sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…[25][26][27][28][29][30] Our previous studies, especially the in vitro ones, showed that daily repeated low-dose irradiation of cells, compared to a single biologically equivalent dose, resulted in significantly higher cell death. 7,17 Experiments conducted on glioma xenografts demonstrated that repeated low-dose irradiation was more effective for inhibiting tumor growth than a single large dose. 7,17 The exact mechanisms underlying HRS are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[25][26][27][28][29][30] Our previous studies, especially the in vitro ones, showed that daily repeated low-dose irradiation of cells, compared to a single biologically equivalent dose, resulted in significantly higher cell death. 7,17 Experiments conducted on glioma xenografts demonstrated that repeated low-dose irradiation was more effective for inhibiting tumor growth than a single large dose. 7,17 The exact mechanisms underlying HRS are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…7,17 Experiments conducted on glioma xenografts revealed that repeated irradiation with low doses (0.8 Gy, three times a day) is more effective than a single dose (2 or 2.4 Gy, once a day) in inhibiting tumor growth. 7,17 Consequently, in 2003, we began a phase II study testing an ultra-fractionated RT for inoperable de novo GBM. 18 The results were promising, and are comparable with the results using the TMZ/RT treatment from the EORTC/NCIC trial.…”
mentioning
confidence: 99%
See 3 more Smart Citations